Navigating Organizational Conflict in Higher Education: The Mediating Role of Transformative Leadership in Enhancing Public Service Quality - Muhammad Mamduh Nuruddin; Sita Husnul Khotimah; Muhammad Iman Kurniawan; Mohamad Gally Tawakal (Qoumun: Jurnal Pengabdian Masyarakat, 2026)
Purpose of the study: This study aimed to analyze the mediating role of transformative leadership in the relationship between organizational conflict and public service quality across higher education environments, where organizational conflict constitutes a complex phenomenon that substantially influences the quality of public services delivered to stakeholders. Methodology: A Systematic Literature Review (SLR) was applied, encompassing the examination of Scopus-indexed and Sinta-indexed scholarly articles published over the past decade. Literature retrieval was conducted in Scopus, Web of Science, Google Scholar, and the Sinta portal using relevant keywords. Main Findings: The findings demonstrate that inadequately managed organizational conflict adversely affects institutional performance and service quality, whereas transformative leadership serves as an effective mediator, converting destructive conflict into constructive engagement. Transformative leadership, characterized by inspirational vision, intellectual stimulation, individualized consideration, and idealized influence, has been demonstrated to enhance organizational cohesion and elevate public service quality. Novelty/Originality of this study: The novelty lies in the explicit positioning of transformative leadership as a mediating mechanism rather than a direct moderator between organizational conflict and public service quality within higher education governance, an approach that advances both conflict management theory and leadership scholarship in the specific context of higher education institutions as public service providers.